Causal Relations Between Macroeconomic Factors and Vietnamese Stock Market Returns: A Johansen Cointegration Test - Nguyen, The Huy (2018)
The purpose of this dissertation is to determine whether the validation of crucial empirical results on causality relationships between stock returns and macroeconomic variables arising from advanced markets is still accurate when applying to developing ones, such as the Vietnamese market. The main method is the Vector Error Correction Model (VECM) and the monthly data sample is collected from March 2008 to December 2016. The results demonstrate there exists a long-run relation between Ho Chi Minh Stock Exchange index and six chosen macroeconomic variables, or equivalently, Vietnamese stock returns and the macroeconomic factors are cointegrated. In particular, there are two negative rela- tions with money supply and lending interest rate while there exists parallelly two positive relations for exchange rate (USD/VND) and industrial production index. The findings from the short-run dynamics, i.e. impulse response and variance decomposition, reveal that the HSX respond inaccurately to an orthogonalised change in, e.g. exchange rate and money supply. However, there still many studies had the same results and these results depended strongly on the studied country’s economic status. Moreover, the results contain the appearance of bidirectional causalities between the changes in exchange rate and industrial production index to the inflation rate, which depict the elaboration of the Vietnamese inflation rate. Lastly, the forecast variance decomposition concludes the strong forecast power of Vietnamese stock index in economic market.